Let's solve the equation \( 3(-2x + 1) = 2(-3x + 2) \).
First, we will distribute on both sides:
-
Distributing on the left side: \[ 3(-2x) + 3(1) = -6x + 3 \]
-
Distributing on the right side: \[ 2(-3x) + 2(2) = -6x + 4 \]
Now the equation becomes: \[ -6x + 3 = -6x + 4 \]
Next, we will try to isolate \( x \) by adding \( 6x \) to both sides: \[ -6x + 6x + 3 = -6x + 6x + 4 \] This simplifies to: \[ 3 = 4 \]
This is a contradiction. Since we end up with a statement that is not true, this indicates that there are no solutions for \( x \).
The final answer is that the equation has no solution.